2016
DOI: 10.1016/j.rmed.2016.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Free asthma medications reduces hospital admissions in Brazil (Free asthma drugs reduces hospitalizations in Brazil)

Abstract: Asthma hospitalization rates significantly decreased in the three-year period after the provision of free medicines to treat asthma. Our findings suggest that the provision of free medications for asthma may have a particular public health impact by its own in developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 12 publications
1
18
0
2
Order By: Relevance
“…The findings also indicated a significant association between knowledge about medication gratuity and self-efficacy in controlling childhood asthma. There were similar results in a study (24) developed in Brazil that demonstrated a 33.57% decrease in hospitalization rates for asthma with the knowledge and access to free medication by the Popular Pharmacy program (beclomethasone and salbutamol). This represented a saving of 51% in financial expenses of the system with asthma-related hospitalizations.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The findings also indicated a significant association between knowledge about medication gratuity and self-efficacy in controlling childhood asthma. There were similar results in a study (24) developed in Brazil that demonstrated a 33.57% decrease in hospitalization rates for asthma with the knowledge and access to free medication by the Popular Pharmacy program (beclomethasone and salbutamol). This represented a saving of 51% in financial expenses of the system with asthma-related hospitalizations.…”
Section: Discussionsupporting
confidence: 75%
“…The maximization of access to medication with guarantees of use according to an action plan associated to an adequate technique for use of inhalation devices is a primordial factor in the management of asthma exacerbations and prevention of severe episodes of the disease (24)(25) .…”
Section: Discussionmentioning
confidence: 99%
“…The lack of use of recommended asthma medications, particularly ICS in this cohort, calls for efforts to increase availability and affordability of asthma medication. Increased access to medicines has been reported to result in better asthma treatment outcomes in some settings, such as the case of Brazil where hospitalisations were significantly reduced with increased access to medications 10. In conclusion, the rates of asthma exacerbations and mortality observed in this study are very high and require strengthening of the health systems to improve asthma care in Uganda.…”
Section: Discussionmentioning
confidence: 60%
“… 1 In Brazil, the hospitalization admission rate due to asthma is 59.85 per 100,000 inhabitants (2012–2014), and such patients have a significantly increased risk of respiratory and all-cause mortality. 2 …”
Section: Introductionmentioning
confidence: 99%